Analysis Of The Success Of Corporate Social Responsibility Activities At PT Ecogreen Oleochemicals Batam - Nabila Sari; Alldila Nadhira Ayu Setyaning (Jurnal Ekonomi, 2024)
This study aims to evaluate and analyze the success of the Corporate Social Responsibility (CSR) program "Pelita" Stunting conducted by PT Ecogreen Oleochemicals Batam. Children need adequate nutrition and good health care to grow and develop optimally. If children's nutritional and health needs are not met, they are at risk of stunting. Through a qualitative approach, this research examines the positive and negative impacts that arise during the implementation of the program, both for the Company and the program participants. The results showed that the "Pelita" Stunting program succeeded in reducing the prevalence of stunting in the Batam City area, improving children's health and development, and strengthening the Company's image in the eyes of the community. However, some negative impacts such as high costs, potential dependency of participants on aid, and challenges in long-term measurement were also identified. To overcome this, PT Ecogreen Oleochemicals Batam can take strategic actions such as collaboration with BKKBN and Health Institutions, improving monitoring and evaluation systems, and education to encourage the independence of program participants. Based on the research results, it can be concluded that the "Pelita" Stunting CSR program has a significant impact in overcoming the problem of stunting. The success of this program shows the importance of the role of CSR in improving the welfare of the community while supporting the sustainability of the company.